Antisocial behavior during adolescence: theory, research and prevention programs - Herrera, Dora (2005)
The existence of several causes of antisocial behavior during adolescence seems to respond, not only to the combination of many risk factors within different levels of human development, but also to cultural and historical processes affecting, in many ways, several generations since their early childhood. This paper revises the main explicative theories about antisocial behavior during adolescence and highlights the theory of the Neuropsychological Taxonomy of the Antisocial Behavior proposed by Terrie E. Moffitt (1993, 1994, 1996, 2003). Moreover, some studies are mentioned due to the fact that they confirm the cross-cultural validity of Moffitt’s theorical model and its  contributions to the design of prevention programs against delinquency for youngsters and adolescents in our context.